Can educational psychology develop to meet the challenges, choices and changes of a 21st century world? - Huxtable, Marie (Psihološka obzorja (Ljubljana), 2022)
Since the 1970s there have been many changes in England to qualifications required to practice as an educational psychologist and the nature of the organisations for which they work. These reflect the slow transformation in societal attitudes to the purposes of public services, education and the role and responsibilities of associated professionals. As a consequence, educational psychology as a distinct field of knowledge and practice is gradually being replaced by the general practice of psychology in Education. I believe that recognising, valuing and working to improve educational psychology as a distinct field of knowledge and practice can make a valuable contribution to the educational development of children and young people as they begin their life-long learning to live satisfying, productive and worthwhile lives for themselves and others as global citizens. Since leaving the profession of educational psychology I have continued to develop theory and practice as a professional educational practitioner supporting the professional development of other educational practitioners working in diverse fields of practice and cultural contexts. I see them faced with the same challenges as educational psychologists to realise their responsibilities as professional educational practitioners working within the constraints imposed by their employers and national government. Education is a values-laden concept and the challenge to us all is not to lose sight of that. I see how members of other professions are creating possibilities of holding fast to values that distinguish educational practice, which I believe educational psychologists might find of use. In this paper I offer an argument for distinguishing between ‘educational psychology as a distinct field of knowledge and practice’ and ‘the practice of psychology in Education’, why it is important and possible ways forward.
Keywords: educational psychology; pedagogi; pedagoška psihologija; poklicni razvoj; professional development; psychologists